2014
DOI: 10.1371/journal.pone.0096220
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Boerhaavia diffusa L. against Mitochondrial Dysfunction in Angiotensin II Induced Hypertrophy in H9c2 Cardiomyoblast Cells

Abstract: Mitochondrial dysfunction plays a critical role in the development of cardiac hypertrophy and heart failure. So mitochondria are emerging as one of the important druggable targets in the management of cardiac hypertrophy and other associated complications. In the present study, effects of ethanolic extract of Boerhaavia diffusa (BDE), a green leafy vegetable against mitochondrial dysfunction in angiotensin II (Ang II) induced hypertrophy in H9c2 cardiomyoblasts was evaluated. H9c2 cells challenged with Ang II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 58 publications
3
33
0
1
Order By: Relevance
“…The ΔΨ m was detected using JC-1 as an indicator which is a lipophilic and cationic dye that accumulates in the mitochondria in a potential-dependent manner. JC-1 emits red fluorescence in normal cells, but the fluorescence will disappear if the ΔΨ m collapses [18]. We showed that either imperatorin or cisplatin alone did not cause significant decrease of ΔΨ m compared with vehicle in the HepG2 model or in the Huh7 model.…”
Section: Imperatorin Enhanced the Cisplatin Cytotoxicity To Hcc Cellsmentioning
confidence: 66%
“…The ΔΨ m was detected using JC-1 as an indicator which is a lipophilic and cationic dye that accumulates in the mitochondria in a potential-dependent manner. JC-1 emits red fluorescence in normal cells, but the fluorescence will disappear if the ΔΨ m collapses [18]. We showed that either imperatorin or cisplatin alone did not cause significant decrease of ΔΨ m compared with vehicle in the HepG2 model or in the Huh7 model.…”
Section: Imperatorin Enhanced the Cisplatin Cytotoxicity To Hcc Cellsmentioning
confidence: 66%
“…Reactive oxygen species play an important role in the development of cardiovascular disease, including hypertension, atherosclerosis, cardiac hypertrophy, ischemia-reperfusion injury and stroke (Paravicini and Touyz 2008;Prathapan et al, 2014;Soumya et al, 2014). In addition to increased free radical production in the failing heart, there is evidence that decreased antioxidant reserves contribute to increased oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Demonstration of antispasmodics/spasmolytic activity of the methanolic root extracts of this plant has further shown the potent use of this time-honoured medicinal plant for the treatment of involuntary muscle spasm caused due to various muscle disorders, including the debilitating symptoms of torticollis, paraplegia and palsy/glossal palsy (Borrelli et al 2006;Mishra et al 2014). A recent report has ignited new expectations about the cardio-protective potential of the ethanolic extract B. diffusa by highlighting its efficacious impact against mitochondrial dysfunction, which has formerly been proven to play a crucial role in triggering the development of cardiac hypertrophy and heart failure (Prathapan et al 2014). The revelation of such multifaceted pharmacokinetics of this plant through the advent of latest tools of combinatorial chemistry is not only the additional therapeutic applications of this ancient medicinal plant in adjunct to its traditional uses, but also boosted its demand in the pharmaceutical industries for future drug development in the years to come.…”
Section: Introductionmentioning
confidence: 99%